Effect of Bovatec® level in supplemental feed on performance and forage utilization characteristics of wintering beef cattle - Cochran, R.C.; Corah, L.R.; Jacques, K.A.; Avery, T.B.; Zoellner, K.O.; Higginbotham, J.F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Various levels of lasalocid (Bovatec®) added to a protein supplement did not improve weight or condition change of beef cows grazing poor quality winter pasture. Similarly, calf birth weight and most forage utilization characteristics (e.g., intake, passage rate, and fermentation characteristics) were not altered by Bovatec level. Although forage digestibility was influenced by Bovatec level, changes were not sufficient to influence performance characteristics.
Keywords: Beef; Bovatec®; Feed performance; Forage utilization